MicroRNA biomarkers in body fluids of prostate cancer patients - Kuner, Ruprecht; Brase, Jan Christoph; Sültmann, Holger; Wuttig, Daniela (Methods, 2013)
The abundance of miRNAs - small non-coding RNAs involved in posttranscriptional regulation of gene expression - in tissues and body fluids of cancer patients hold great promise to identify specific biomarkers, which may be useful for early diagnosis as well as to predict the clinical outcome and treatment response. For the extraction and quantification of miRNAs from cells and tissues, present technologies for transcriptome analyses like microarrays, quantitative real-time PCR or next generation sequencing can be applied. However, the analyses of miRNAs in body fluids like serum or urine is still a challenge with respect to the nucleic acid recovery from very limited sources of biomaterial, normalization strategies and validation using independent technologies. The presence of specific miRNA patterns in body fluids like serum of cancer patients suggests a promising role of these molecules as surrogate markers. However, the majority of miRNA studies were addressed in relatively small patient cohorts limiting the validity and the clinical application of potential miRNA biomarkers or signatures. We reflect the critical steps to translate miRNA biomarker into clinical routine diagnostics and present future aspects for the fast, robust and standardized quantification of miRNAs in body fluids.